2023
DOI: 10.2147/ijn.s413831
|View full text |Cite
|
Sign up to set email alerts
|

Engineered Plant-Derived Nanovesicles Facilitate Tumor Therapy: Natural Bioactivity Plus Drug Controlled Release Platform

Xiaohang Chen,
Shuaiqi Ji,
Yuxiang Yan
et al.

Abstract: Tumors are the second-most common disease in the world, killing people at an alarming rate. As issues with drug resistance, lack of targeting, and severe side effects are revealed, there is a growing demand for precision-targeted drug delivery systems. Plant-derived nanovesicles (PDNVs), which arecomposed of proteins, lipids, RNA, and metabolites, are widely distributed and readily accessible. The potential for anti-proliferative, pro-apoptotic, and drug-resistant-reversing effects on tumor cells, as well as t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(3 citation statements)
references
References 125 publications
(258 reference statements)
0
3
0
Order By: Relevance
“…Consequently, attention has shifted towards natural plant sources as alternatives to address the limitations associated with mammalian-derived exosomes. The utilization of plant-derived exosomes is particularly appealing due to their cost-effectiveness, biocompatibility, intrinsic anti-tumor properties, and the feasibility of industrial-scale manufacturing ( Alzahrani et al, 2023 ; Chen et al, 2023 ; Xu et al, 2023 ). These features make them as emerging nanomedical agents of great interest in therapeutic research across multiple cancer types ( Guglielmi et al, 2020 ; Stanly et al, 2020 ; Özkan et al, 2021 ; Chen et al, 2022 ).…”
Section: Discussionmentioning
confidence: 99%
“…Consequently, attention has shifted towards natural plant sources as alternatives to address the limitations associated with mammalian-derived exosomes. The utilization of plant-derived exosomes is particularly appealing due to their cost-effectiveness, biocompatibility, intrinsic anti-tumor properties, and the feasibility of industrial-scale manufacturing ( Alzahrani et al, 2023 ; Chen et al, 2023 ; Xu et al, 2023 ). These features make them as emerging nanomedical agents of great interest in therapeutic research across multiple cancer types ( Guglielmi et al, 2020 ; Stanly et al, 2020 ; Özkan et al, 2021 ; Chen et al, 2022 ).…”
Section: Discussionmentioning
confidence: 99%
“…Some microbes produce beneficial metabolites through metabolism, such as short-chain fatty acids, which can promote gut health and immune system function [ 53 ]. The series of effects played by altering the metabolism of bacteria is also one of the main activities of PDNVs in regulating the microbial community [ 71 ]. A study found that lemon-derived nanovesicles enhanced the level of lactate production by lactic acid bacteria, thereby inhibiting the growth of Clostridium difficile .…”
Section: Bioactivity: Microbial Regulation By Pdnvsmentioning
confidence: 99%
“…Consequently, attention has shifted towards natural plant sources as alternatives to address the limitations associated with mammalian-derived exosomes. The utilization of plantderived exosomes is particularly appealing due to their cost-effectiveness, biocompatibility, intrinsic anti-tumor properties, and the feasibility of industrial-scale manufacturing (Alzahrani et al, 2023;Chen et al, 2023;Xu et al, 2023). These features make them as emerging nanomedical agents of great interest in therapeutic research across multiple cancer types (Guglielmi et al, 2020;Stanly et al, 2020;Özkan et al, 2021;Chen et al, 2022).…”
Section: Discussionmentioning
confidence: 99%